Feedlot conditions and their influence on blood parameter values in Merino lambs in Extremadura, Spain over a specific time-period - FERNÁNDEZ, S.; GALAPERO, J.; REY, J.; PÉREZ, C. J.; RAMOS, A.; GÓMEZ, L. (Journal of the Hellenic Veterinary Medical Society, 2018)
It has been suggested that the evaluation of specific blood parameters can be used as indicators of animal health and welfare. The aim of this study was to determine possible differences in these parameters at the beginning and at the end of the feedlot period and to analyse the influence of feedlot conditions on these animals. Blood parameter ranges can vary widely depending on factors such as transport, handling and feedlot. Four hundred and ten fattening lambs were studied to establish average values of different blood parameters. For data analysis, descriptive statistics and paired t-tests were used. The results of the current study indicate that mean values of Haematocrit, Cellular Haemoglobin Concentration and Cortisol levels were outside of the normal range, both at the beginning of the feedlot period and at upon leaving the feedlot. Higher mean values of MCHC, Urea, Total Proteins and Cortisol levels were observed at the end compared to the beginning of the feedlot period. On the other hand, Haematocrit, Mean Corpuscular Volume (MCV), Eosinophils and Creatine phosphokinase (CPK) were at higher mean values at the beginning of the feedlot period. Elevations in some blood parameters that are associated with acute stress states were raised in slaughter lambs during the feedlot period, transport and handling.